Magnetic porous microsphere for in-vitro diagnosis and preparation method thereof
By adopting a multi-step preparation method in in vitro diagnosis, using styrene polymerized monomers and magnetic nanomaterials, the magnetic content and magnetic response of porous magnetic beads have been successfully improved, and the problems of insufficient magnetic content and long preparation period in the prior art have been solved, thereby achieving efficient and stable in vitro diagnostic microsphere preparation.
Patent Information
- Application Number
- CN202510050113.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
AI Technical Summary
The insufficient magnetic content, low magnetic response and long preparation cycle of existing porous magnetic beads affect the accuracy and production efficiency of in vitro diagnosis.
Porous polystyrene microspheres were prepared by dispersing polymerization method, and magnetic nanomaterials were synthesized by co-precipitation method under alkaline conditions. The magnetic nanomaterial was loaded on the surface and pores of the porous polystyrene microspheres by multi-step seed growth method. Finally, functional groups were introduced through monomer swelling polymerization method to obtain magnetic porous microspheres.
The magnetic content and magnetic response of magnetic porous microspheres are improved, the preparation cycle is shortened, and the production efficiency and application performance of the product are improved.
Smart Images

Figure CN119819269A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of micro-nano material preparation, and specifically relates to a magnetic porous microsphere for in vitro diagnosis and a preparation method thereof. Background Art
[0002] In vitro diagnosis (IVD) is a technical means to obtain clinical diagnostic information by testing human samples outside the human body. It has the advantages of being fast, convenient and effective. However, its upstream reagent raw materials account for a small proportion of the domestic market. The quality of in vitro diagnostic reagent raw materials determines the stability and sensitivity of the diagnosis. Micro-nano porous materials have a much higher specific surface area and unique pore structure than macroscopic materials, which can provide a large number of active sites. Not only can they modify more molecules on their surface, but they can also encapsulate more magnetic substances inside their pores, thereby increasing the magnetic content and improving the magnetic stability, fundamentally solving problems such as poor sensitivity. These micro-nano porous materials with different molecules modified on the surface can selectively detect small molecules, nucleic acids, proteins and microorganisms, making them play a vital role in in vitro diagnostic applications such as bioanalysis and biosensors.
[0003] Taking micro-nano porous magnetic spheres as an example, the main barriers to domestic raw materials are: 1) single particle size and poor dispersibility. The single particle size and poor dispersibility will affect the binding efficiency of micro-nano porous magnetic spheres and protein molecules, and thus affect the accuracy and stability of in vitro diagnosis. Monodispersity is the basis for the binding of micro-nano porous magnetic spheres with protein molecules. The preparation of micro-nano porous magnetic spheres with the same excellent performance at different sizes is one of the core goals pursued by all domestic reagent raw material manufacturers. At present, most dispersed structure magnetic beads have the disadvantage of poor dispersibility. 2) Low cross-linking degree, the holes of the porous spheres only exist on the outer surface. Porous organic materials are generally divided into the following categories according to their different synthesis methods: self-polymerized microporous polymers, hyper-cross-linked polymers, covalent organic networks and conjugated microporous polymers. Hyper-cross-linked polymers are a type of porous material prepared based on Friedel-Crafts alkylation reaction. Due to its advantages such as high specific surface area, mild synthesis conditions, and wide monomer sources, it is still a huge challenge to prepare hyper-cross-linked microporous polymers with stable morphology through streamlined technology. 3) Low magnetic content. In the field of in vitro diagnostic chemiluminescence, low magnetic content will directly affect the separation speed. Slow separation speed will lead to magnetic loss, which will lead to a decrease in luminescence value and reduce the sensitivity of diagnosis. 4) The preparation cycle of porous microspheres is long. The currently commonly used methods for preparing porous microspheres by swelling polymerization require a reaction of more than 24 hours, which leads to a long preparation cycle, is not conducive to commercial mass production, and affects product production efficiency. 5) Poor suspension and easy sedimentation. The suspension performance of magnetic balls directly affects the amount of binding with protein molecules. Poor suspension will cause magnetic beads to aggregate, which will affect the test sensitivity and stability.
[0004] Some scholars use ferrite as the magnetic core and vinyl siloxane hydrolyzate as the shell to prepare magnetic spheres, in which the ferrite used is nanometer-level. During the action of vinyl siloxane, since the concentrations of both are relatively high in the early stage, it is easy to generate disordered microspheres and the number of surface functional groups is unevenly distributed, which causes the aggregation between magnetic beads and the increase of nonspecific adsorption in the later polymerization reaction, and it is difficult to obtain monodisperse and stable magnetic spheres. Some people also use polystyrene microspheres as seed microspheres to prepare porous polystyrene microspheres by seed two-step swelling method, but the reaction time is long. The first step of swelling needs to react for 6-18h, and the second step of swelling needs to react for 12-36h. The preparation cycle is too long, which affects the production efficiency of the product and is not conducive to conversion and subsequent amplification. At the same time, the holes of the porous microspheres prepared are mostly concentrated on the surface of the microspheres, and even only the outer surface has a slightly porous structure, which is not conducive to the entry of magnetic substances. The magnetic substances are only coated on the surface, and the magnetic content cannot be well improved, and the advantages of porous microspheres cannot be fully utilized. Others have infiltrated ferric oleate molecules into polymer microspheres, and then decomposed the ferric oleate by increasing the temperature to synthesize magnetic ferroferric oxide nanoparticles inside the microspheres, and then obtained superparamagnetic polymer microspheres. However, during the preparation process, polystyrene microspheres need to undergo a high temperature process. After high temperature, polystyrene microspheres are very likely to adhere to each other and form polymers, which is not conducive to their application in the field of in vitro diagnosis. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a magnetic porous microsphere for in vitro diagnosis and a preparation method thereof, so as to solve the technical problems of insufficient magnetic content, low magnetic response and long preparation cycle of the porous magnetic beads.
[0006] To achieve the above-mentioned purpose, the technical scheme adopted by the present invention is: to provide a method for preparing magnetic porous microspheres for in vitro diagnosis, firstly using styrene as a polymerization monomer and adopting a dispersion polymerization method to prepare porous polystyrene microspheres; selecting iron salt as a precursor, synthesizing magnetic nanomaterials by a coprecipitation method under alkaline conditions, and loading the magnetic nanomaterials on the surface and pores of the porous polystyrene microspheres by a multi-step seed growth method to obtain magnetic beads; finally, introducing functional groups on the surface of the magnetic spheres by a monomer swelling polymerization method using monomers containing functional groups to obtain magnetic porous microspheres.
[0007] On the basis of the above technical solution, the present invention can also be improved as follows:
[0008] Furthermore, the magnetic nanomaterial is ferroferric oxide, ferric hydroxide, r-ferrous oxide, ferrite, cobalt oxide, manganese oxide, iron-nickel alloy or iron-aluminum alloy.
[0009] Further, the method specifically includes the following steps:
[0010] S1. Preparation of polystyrene-based spheres: dissolving an initiator, a stabilizer and a polymerization monomer in an organic solvent at a mass ratio of 0.01-0.5:0.01-0.1:3-10, then heating to 45-55° C. for reaction for 5-7 hours, centrifuging, and drying to obtain polystyrene-based spheres; the polymerization monomer is styrene;
[0011] S2, preparing porous polystyrene microspheres;
[0012] S201, mixing a cross-linking agent, a polymerized monomer 1, a polymerized monomer 2, a porogen and a composite emulsifier uniformly to obtain a solution 1; the ratio of the cross-linking agent, the polymerized monomer 1, the polymerized monomer 2, the porogen and the composite emulsifier is 0.05-0.15 g: 2-3 mL: 1-2 mL: 2-3 mL: 25-35 mL; the polymerized monomer 2 is hydroxyethyl methacrylate (MHEA);
[0013] S202, dispersing polystyrene base balls in a composite emulsifier at a ratio of 0.2-0.25 g: 110-130 mL at 60-80° C. to obtain solution 2; adding solution 1 to solution 2 at a volume ratio of 35-40: 110-130, reacting at 60-80° C. for 1-3 hours to obtain solution 3;
[0014] S203, mixing the composite emulsifier, the crosslinking agent, the porogen, the initiator and the solution three in a volume ratio of 8-12:11-14:1-1.5:0.06-0.1:150-165, and then reacting at 80-90° C. for 0.1-1h;
[0015] S204, centrifuging and drying to obtain porous polystyrene microspheres;
[0016] S3, magnetospheric envelope;
[0017] S301, dispersing porous polystyrene microspheres in a composite emulsifier, then adding an iron salt solution under a protective atmosphere, stirring and reacting at 0-70°C for 0.5-1.5h, then adjusting the pH value of the reaction system to 9-12, continuing the reaction for 4-6h, and finally magnetically separating to obtain a magnetic nanomaterial; the ratio of porous polystyrene microspheres, composite emulsifier and iron salt solution is 0.4-0.6g:15-25mL:5-7mL;
[0018] S302, dispersing the magnetic nanomaterial in a composite emulsifier, and repeating step S301 to obtain high magnetic content, multi-layer coated magnetic beads;
[0019] S4. Coating functional groups: In order to make the magnetic layer more stable, the carboxyl group is coated on the outside of the magnetic layer by using the monomer swelling method, specifically:
[0020] S401, mixing a composite emulsifier, an initiator, a polymerization monomer 1, a crosslinking agent and a functional monomer in a ratio of 18-22 mL: 0.05-0.15 g: 0.5-1.5 mL: 200-400 μL: 300-500 μL to obtain a solution 4; the functional monomer is styrene, divinylbenzene, 2,4-dichlorostyrene, acrylic acid, methacrylic acid, acrylamide, methyl methacrylate, methyl acrylate, ethyl acrylate, vinyl acetate or glycidyl methacrylate;
[0021] S402, disperse the magnetic beads in the composite emulsifier, then mix evenly with solution four, then heat to 60-80°C for reaction for 1.5-2.5h, centrifuge, and dry to obtain magnetic porous microspheres for in vitro diagnosis; the ratio of magnetic beads, composite emulsifier and solution four is 0.3-0.7g:30-50mL:20-25mL.
[0022] Furthermore, the initiator is at least one of ammonium persulfate, benzoyl peroxide, potassium persulfate, sodium persulfate, sodium sulfite, azobisisobutyronitrile, azobiscyanovaleric acid, sodium bisulfite and dicumyl peroxide; and the stabilizer is polyvinyl pyrrolidone.
[0023] Furthermore, the drying temperature is 60-80°C and the drying time is 8-12h.
[0024] Furthermore, the crosslinking agent is divinylbenzene or tert-butyl peroxide; the porogen is at least one of toluene, ethylbenzene, n-hexane, cyclohexanol, n-heptane, n-octane, n-heptanol, di(2-ethylhexyl) phosphate and phthalate.
[0025] Furthermore, the composite emulsifier is prepared by dissolving component A and component B in water at a mass ratio of 0.01-0.12:0.05-1.2; component A is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium stearate and oleate; and component B is at least one of PVP k30, PVP k60, PVP k80 and PVA.
[0026] Furthermore, the protective atmosphere gas is nitrogen.
[0027] Furthermore, the solutes in the iron salt solution are ferric chloride and ferrous sulfate, and the mass ratio of ferric chloride to ferrous sulfate is 1-2:2.
[0028] Furthermore, the reagent used to adjust the pH value in S301 is ammonia water, sodium hydroxide, potassium hydroxide, sodium alcoholate or potassium alcoholate.
[0029] The invention also discloses magnetic porous microspheres for in vitro diagnosis prepared by the preparation method.
[0030] The invention also discloses the application of the magnetic porous microspheres for in vitro diagnosis in the preparation of in vitro diagnosis reagents.
[0031] The beneficial effects of the present invention are:
[0032] 1. The present invention reduces the weight of porous polystyrene microspheres themselves by preparing a porous structure to make the suspension better, and also can provide a larger specific surface area for magnetic layer coating; and the prepared magnetic porous microspheres have the advantages of uniform particle size, small coefficient of variation, and large specific surface area, and can better combine with antigens and antibodies, so as to perform in vitro diagnostic function detection such as nucleic acid extraction and chemiluminescence.
[0033] 2. The pores of the porous highly cross-linked polystyrene microspheres prepared by the present invention are not only distributed on the surface of the shell layer, but also evenly distributed in the internal core layer, which can combine more magnetic particles, and use multi-step seed growth for magnetic layer coating, so that the magnetic content is greatly improved, and the performance of the final product is improved. And the pore size, porosity and particle size can be regulated according to the actual application requirements. The finally prepared magnetic porous microspheres have slow sedimentation speed, good magnetic separation efficiency, good monodispersity, uniform particle size distribution, high magnetic content, adjustable surface functional group content and functional layer thickness, and have a wide range of application scenarios.
[0034] 3. The present invention shortens the swelling polymerization reaction time of porous microspheres, and the preparation of highly cross-linked porous polystyrene microspheres can be achieved in 3 hours. The preparation cycle is short, the production efficiency is high, and it is conducive to conversion and subsequent scale-up production. In addition, the reaction conditions are mild and very environmentally friendly; the preparation process is relatively simple, highly operable, and highly efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a flow chart of the method of the present invention;
[0036] Figure 2 are SEM images of polystyrene-based spheres, wherein Figure (a) is a SEM image of the polystyrene-based sphere PS-1 prepared when the styrene dosage is 6 mL, Figure (b) is a SEM image of the polystyrene-based sphere PS-2 prepared when the styrene dosage is 1.5 mL, Figure (c) is a SEM image of the polystyrene-based sphere PS-3 prepared when the styrene dosage is 3 mL, and Figure (d) is a SEM image of the polystyrene-based sphere PS-4 prepared when the styrene dosage is 4.5 mL;
[0037] Figure 3 is the particle size distribution diagram of polystyrene based spheres PS-1;
[0038] Figure 4 is the particle size distribution diagram of polystyrene-based spheres PS-2;
[0039] Figure 5 is the particle size distribution diagram of polystyrene-based spheres PS-3;
[0040] Figure 6 is the particle size distribution diagram of polystyrene-based spheres PS-4;
[0041] Figure 7 Figure 1 is a SEM image of porous polystyrene microspheres, wherein Figure (a) is a SEM image of porous polystyrene microspheres PPS-1 prepared when the toluene dosage is 0.7 mL, Figure (b) is a SEM image of porous polystyrene microspheres PPS-2 prepared when the toluene dosage is 1.38 mL, and Figure (c) is a SEM image of porous polystyrene microspheres PPS-3 prepared when the toluene dosage is 2.76 mL;
[0042] Figure 8 This is the SEM image of porous polystyrene microspheres PPS-3 after being coated with multiple magnetic layers;
[0043] Fig. 9 TEM images of magnetic beads after being coated with multiple magnetic layers, where (a) is the TEM image of magnetic beads, (b) is the high-angle annular dark field (STEM-HADDF) mode image, (c) is the X-ray energy spectrum element summary (EDS-Mapping) image, and (d) is the iron element EDS-Mapping image;
[0044] Fig.10 is the SEM image of magnetic porous microspheres;
[0045] Fig.11 TEM images of magnetic porous microspheres, wherein (a) is a TEM image of magnetic porous microspheres AA-1 prepared when the amount of AA is 300 μL, (b) is a TEM image of magnetic porous microspheres AA-2 prepared when the amount of AA is 400 μL, (c) is a TEM image of magnetic porous microspheres AA-3 prepared when the amount of AA is 500 μL, and (d) is a TEM image of magnetic porous microspheres AA-4 prepared when the amount of AA is 800 μL;
[0046] Fig.12 This is the infrared test (FT-IR) spectrum of magnetic porous microspheres;
[0047] Fig.13 The figure is a comparison diagram of the magnetic adsorption separation time of the control magnetic beads, wherein Figure (a) is a physical picture of the control magnetic beads before magnetic separation, and Figure (b) is a physical picture of the control magnetic beads after magnetic separation;
[0048] Fig.14 The figure is a comparison chart of the magnetic adsorption separation time of the magnetic porous microsphere AA-1, wherein figure (a) is a physical picture of AA-1 before magnetic separation, and figure (b) is a physical picture of AA-1 after magnetic separation;
[0049] Fig.15The natural sedimentation display diagrams of the magnetic porous microspheres AA-1, AA-2 and control magnetic beads, wherein Figure (a) is a physical comparison diagram of the samples after ultrasonic homogenization and before sedimentation, and Figure (b) is a physical comparison diagram of the samples after sedimentation. DETAILED DESCRIPTION
[0050] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.
[0051] The composite emulsifier used below is SDBS-PVA solution, in which the mass ratio of SDBS, PVA and water is 1:5:100.
[0052] Example 1
[0053] A method for preparing magnetic porous microspheres for in vitro diagnosis, the process is as follows Figure 1 As shown, the following steps are included:
[0054] S1, preparing polystyrene-based spheres (PS);
[0055] S101, dissolving 0.8 g of azobisisobutyronitrile (AIBN) and 0.6 g of polyvinyl pyrrolidone in a mixed solution consisting of 10 mL of deionized water and 30 mL of anhydrous ethanol, and then adding 6 mL of styrene (St) and mixing well;
[0056] S102, heating the reaction system to 50° C. and reacting for 6 h, then placing in an ice bath to stop the reaction, centrifuging, washing, and finally drying the washed product under vacuum at 70° C. for 10 h to obtain polystyrene-based spheres (PS);
[0057] S2, preparing porous polystyrene microspheres (PPS);
[0058] S201, dissolving 0.1 g of tert-butyl peroxide in 2 mL of methanol, and then mixing with 2.5 mL of styrene (St), 1.6 mL of hydroxyethyl methacrylate (MHEA), 2.76 mL of toluene and 15 mL of SDBS-PVA solution to obtain solution 1;
[0059] S202, dispersing 0.22 g of polystyrene base spheres (PS) in 120 mL of SDBS-PVA solution at 70° C. to obtain solution 2, then adding 22 mL of solution 1 dropwise to 120 mL of solution 2, and reacting at the same temperature for 2 h to obtain solution 3;
[0060] S203, 10 mL SDBS-PVA solution, 13.2 mL divinylbenzene (DVB), 1.38 mL toluene and 0.08 g ammonium persulfate (APS) were mixed evenly, and then 155 mL of solution 3 was added using a peristaltic pump (peristaltic rate was 5 mL / min) under stirring at 200 rpm, and then the temperature of the reaction system was raised to 85°C, and the stirring reaction was continued for 30 min;
[0061] S204, taking the mixed solution obtained in S203 as solution 3, and repeating S203;
[0062] S205, placing the reaction solution obtained in S204 in an ice bath to stop the reaction, centrifuging, washing, and finally vacuum drying the washed product at 70° C. for 10 h to obtain porous polystyrene microspheres (PPS);
[0063] S3, magnetospheric envelope;
[0064] S301, 0.5g of porous polystyrene microspheres (PPS) were dispersed in 20mL of SDBS-PVA solution, and then 0.45g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.57g of ferrous sulfate heptahydrate (FeSO4·7H2O) were dissolved in 5mL of H2O under a nitrogen atmosphere to obtain an iron salt solution; the iron salt solution was then injected into the porous polystyrene microsphere solution using a syringe, and the reaction was stirred at 25°C and 200rpm for 1h; the pH value of the reaction system was then adjusted to 9 with 5.76wt% of ammonia water, the reaction was continued for 5h, and finally magnetic separation was performed to obtain a magnetic nanomaterial;
[0065] S302, dispersing the magnetic nanomaterial in the SDBS-PVA solution, repeating step S301, and finally obtaining multi-layer coated magnetic beads;
[0066] S4, coating functional group;
[0067] S401, dissolving 0.5 g SDBS, 0.15 g PVA and 0.1 g azobisisobutyronitrile (AIBN) in 20 mL deionized water, then adding 1 mL styrene (St), 300 μL divinylbenzene (DVB) and 400 μL acrylic acid (AA) and mixing well to obtain solution 4;
[0068] S402, disperse 0.5g magnetic beads in 40mL SDBS-PVA solution, then mix evenly with 23mL solution four, then heat to 70°C, react at 300rpm for 2h, filter, magnetically separate, wash the obtained precipitate, and finally vacuum dry at 70°C for 10h to obtain magnetic porous microspheres.
[0069] Example 2
[0070] A method for preparing magnetic porous microspheres for in vitro diagnosis, the process is as follows Figure 1 As shown, the following steps are included:
[0071] S1, preparing polystyrene-based spheres (PS);
[0072] S101, dissolving 0.7 g potassium persulfate and 0.5 g polyvinyl pyrrolidone in a mixed solution consisting of 10 mL deionized water and 30 mL anhydrous ethanol, and then adding 7 mL styrene (St) and mixing well;
[0073] S102, heating the reaction system to 45°C and reacting for 7 hours, then placing in an ice bath to stop the reaction, centrifuging, washing, and finally drying the washed product under vacuum at 60°C for 12 hours to obtain polystyrene-based spheres (PS);
[0074] S2, preparing porous polystyrene microspheres (PPS);
[0075] S201, dissolving 0.15 g of tert-butyl peroxide in 2 mL of methanol, and then mixing with 2 mL of styrene (St), 2 mL of hydroxyethyl methacrylate (MHEA), 3 mL of n-hexane and 15 mL of SDBS-PVA solution to obtain solution 1;
[0076] S202, dispersing 0.2 g of polystyrene base spheres (PS) in 120 mL of SDBS-PVA solution at 60° C. to obtain solution 2, then adding 35 mL of solution 1 dropwise to 130 mL of solution 2, and reacting at the same temperature for 1 h to obtain solution 3;
[0077] S203, 8 mL SDBS-PVA solution, 11 mL divinylbenzene (DVB), 1.5 mL n-hexane and 0.1 g ammonium persulfate (APS) were mixed evenly, and then 165 mL solution 3 was added using a peristaltic pump (peristaltic rate was 7 mL / min) under stirring at 200 rpm, and then the temperature of the reaction system was raised to 80°C, and the stirring reaction was continued for 60 min;
[0078] S204, taking the mixed solution obtained in S203 as solution 3, and repeating S203;
[0079] S205, placing the reaction solution obtained in S204 in an ice bath to stop the reaction, centrifuging, washing, and finally vacuum drying the washed product at 60° C. for 12 h to obtain porous polystyrene microspheres (PPS);
[0080] S3, magnetospheric envelope;
[0081] S301, 0.4g of porous polystyrene microspheres (PPS) were dispersed in 20mL of SDBS-PVA solution, and then 0.45g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.57g of ferrous sulfate heptahydrate (FeSO4·7H2O) were dissolved in 5mL of H2O under a nitrogen atmosphere to obtain an iron salt solution; the iron salt solution was then injected into the porous polystyrene microsphere solution using a syringe, and the reaction was stirred at 0°C and 200rpm for 1.5h; the pH value of the reaction system was then adjusted to 11 with 5.76wt% of ammonia water, the reaction was continued for 6h, and finally magnetic separation was performed to obtain a magnetic nanomaterial;
[0082] S302, dispersing the magnetic nanomaterial in the SDBS-PVA solution, repeating step S301, and finally obtaining multi-layer coated magnetic beads;
[0083] S4, coating functional group;
[0084] S401, dissolving 0.5 g SDBS, 0.15 g PVA and 0.05 g azobisisobutyronitrile (AIBN) in 20 mL deionized water, then adding 1.5 mL styrene (St), 200 μL divinylbenzene (DVB) and 500 μL acrylic acid (AA) and mixing well to obtain solution 4;
[0085] S402, disperse 0.3g magnetic beads in 40mL SDBS-PVA solution, then mix evenly with 20mL solution four, then heat to 80°C, react at 300rpm for 1.5h, filter, magnetically separate, wash the obtained precipitate, and finally vacuum dry at 60°C for 12h to obtain magnetic porous microspheres.
[0086] Example 3
[0087] A method for preparing magnetic porous microspheres for in vitro diagnosis, the process is as follows Figure 1 As shown, the following steps are included:
[0088] S1, preparing polystyrene-based spheres (PS);
[0089] S101, dissolving 0.9 g of sodium sulfite and 0.7 g of polyvinyl pyrrolidone in a mixed solution consisting of 10 mL of deionized water and 30 mL of anhydrous ethanol, and then adding 5 mL of styrene (St) and mixing well;
[0090] S102, heating the reaction system to 55° C. and reacting for 5 h, then placing in an ice bath to stop the reaction, centrifuging, washing, and finally vacuum drying the washed product at 80° C. for 8 h to obtain polystyrene-based spheres (PS);
[0091] S2, preparing porous polystyrene microspheres (PPS);
[0092] S201, dissolving 0.05 g of tert-butyl peroxide in 2 mL of methanol, and then mixing with 3 mL of styrene (St), 1 mL of hydroxyethyl methacrylate (MHEA), 2 mL of toluene and 15 mL of SDBS-PVA solution to obtain solution 1;
[0093] S202, dispersing 0.25 g of polystyrene-based spheres (PS) in 120 mL of SDBS-PVA solution at 80° C. to obtain solution 2, then adding 40 mL of solution 1 dropwise to 110 mL of solution 2, and reacting at the same temperature for 3 h to obtain solution 3;
[0094] S203, 12 mL SDBS-PVA solution, 14 mL divinylbenzene (DVB), 1 mL toluene and 0.06 g ammonium persulfate (APS) were mixed evenly, and then 150 mL of solution 3 was added using a peristaltic pump (peristaltic rate was 9 mL / min) under stirring at 200 rpm, and then the temperature of the reaction system was raised to 90°C, and the stirring reaction was continued for 0.1 h;
[0095] S204, taking the mixed solution obtained in S203 as solution 3, and repeating S203;
[0096] S205, placing the reaction solution obtained in S204 in an ice bath to stop the reaction, centrifuging, washing, and finally drying the washed product under vacuum at 80° C. for 8 h to obtain porous polystyrene microspheres (PPS);
[0097] S3, magnetospheric envelope;
[0098] S301, 0.6 g of porous polystyrene microspheres (PPS) were dispersed in 20 mL of SDBS-PVA solution, and then 0.45 g of ferric chloride hexahydrate (FeCl3·6H2O) and 0.57 g of ferrous sulfate heptahydrate (FeSO4·7H2O) were dissolved in 5 mL of H2O under a nitrogen atmosphere to obtain an iron salt solution; the iron salt solution was then injected into the porous polystyrene microsphere solution using a syringe, and the reaction was stirred at 70° C. and 200 rpm for 0.5 h; the pH value of the reaction system was then adjusted to 12 with sodium hydroxide, and the reaction was continued for 4 h, and finally magnetic separation was performed to obtain a magnetic nanomaterial;
[0099] S302, dispersing the magnetic nanomaterial in the SDBS-PVA solution, repeating step S301, and finally obtaining multi-layer coated magnetic beads;
[0100] S4, coating functional group;
[0101] S401, dissolving 0.5 g SDBS, 0.15 g PVA and 0.15 g azobisisobutyronitrile (AIBN) in 20 mL deionized water, then adding 0.5 mL styrene (St), 400 μL divinylbenzene (DVB) and 300 μL acrylic acid (AA) and mixing well to obtain solution 4;
[0102] S402, disperse 0.7g magnetic beads in 40mL SDBS-PVA solution, then mix evenly with 25mL solution four, then heat to 60°C, react at 300rpm for 2.5h, filter, magnetically separate, wash the obtained precipitate, and finally vacuum dry at 80°C for 8h to obtain magnetic porous microspheres.
[0103] Experimental Example 1
[0104] 1. Effect of styrene on the particle size of polystyrene-based spheres
[0105] By changing the amount of styrene, a polymerized monomer, in step S101, the effect of styrene on the particle size of polystyrene-based spheres was explored. Specifically, the amount of styrene in step S101 was set to 6, 1.5, 3, and 4.5 mL, respectively, to obtain polystyrene-based spheres PS-1, PS-2, PS-3, and PS-4.
[0106] Figure 2 Figure 2 is the SEM image of the polystyrene-based spheres, wherein Figure (a) is the SEM image of the polystyrene-based sphere PS-1 prepared when the styrene dosage is 6 mL, Figure (b) is the SEM image of the polystyrene-based sphere PS-2 prepared when the styrene dosage is 1.5 mL, Figure (c) is the SEM image of the polystyrene-based sphere PS-3 prepared when the styrene dosage is 3 mL, and Figure (d) is the SEM image of the polystyrene-based sphere PS-4 prepared when the styrene dosage is 4.5 mL. Figure 3-Figure 6 These are the particle size distribution diagrams of polystyrene base balls PS-1, PS-2, PS-3 and PS-4, and the base ball particle sizes correspond to 0.80μm, 1.05μm, 1.30μm and 1.60μm, respectively. It can be seen from the figure that the base balls are evenly dispersed, and the particle size is uniform and adjustable, and the particle size of the base balls can be adjusted according to actual needs.
[0107] 2. Effect of toluene on porous polystyrene microspheres
[0108] Based on the polystyrene-based sphere PS-4 prepared when the amount of styrene was 4.5 mL, the amount of porogen toluene in step S201 was changed to explore the effect of toluene on the porous polystyrene microspheres. Specifically, the amount of toluene in step S201 was set to 0.7, 1.38 and 2.76 mL, respectively, to obtain porous polystyrene microspheres PPS-1, PPS-2 and PPS-3.
[0109] Figure 7 Figure 1 is the SEM image of porous polystyrene microspheres, where (a) is the SEM image of porous polystyrene microspheres PPS-1 prepared when the toluene dosage is 0.7 mL, (b) is the SEM image of porous polystyrene microspheres PPS-2 prepared when the toluene dosage is 1.38 mL, and (c) is the SEM image of porous polystyrene microspheres PPS-3 prepared when the toluene dosage is 2.76 mL. The average particle size of PPS-1 is 2.8 μm, and the average pore size is 0.04 μm; the average particle size of PPS-2 is 3.1 μm, and the average pore size is 0.08 μm; the average particle size of PPS-3 is 2.2 μm, and the average pore size is 0.14 μm. It can be seen from the figure that the particle size of porous polystyrene microspheres is uniform and adjustable, showing a monodisperse state, and the pore size and porosity can also be adjusted. The pores are deeper than the inside of the ball, showing a highly cross-linked porous state. This shows that by strictly controlling the reaction rate using a peristaltic pump and changing the dosage of the porogen, highly cross-linked porous microspheres with different particle sizes and porosities can be obtained.
[0110] Figure 8 This is the SEM image of porous polystyrene microspheres PPS-3 after being coated with multiple magnetic layers; Fig. 9 The TEM images of magnetic beads after being coated with multiple magnetic layers, where (a) is the TEM image of magnetic beads, (b) is the high-angle annular dark field (STEM-HADDF) mode image, (c) is the X-ray energy spectrum element summary (EDS-Mapping) image, and (d) is the iron element EDS-Mapping image. It can be seen from the figure that the magnetic nanoparticles are coated on the surface of the magnetic beads and inside the pores, and the coating state is stable, without a large number of magnetic particles scattered; the relatively large pores are conducive to the enrichment of magnetic substances inside the pores, while increasing the magnetic content, the magnetic particles are sealed inside, which is conducive to improving the magnetic stability. The iron content in the magnetic beads of the sample PPS-3 after being coated with a magnetic layer was measured by ICP, and the magnetic content of the magnetic beads prepared by the present invention was measured to be 15.18%. Compared with the magnetic beads synthesized by the ordinary one-step co-precipitation method, the magnetic content has been greatly improved, and the magnetic content has been increased by two times compared with the commercial control magnetic beads (8.4%). From the TEM image, it can be seen that there are abundant superparamagnetic nanoparticles both inside and on the surface of the porous microspheres, and the external magnetic coating is more, showing a core-shell structure.
[0111] 3. Effect of acrylic acid on magnetic porous microspheres
[0112] Based on the porous polystyrene microspheres PPS-3 prepared when the amount of toluene was 4.5 mL, the amount of functional monomer acrylic acid (AA) in step S401 was changed to explore the effect of AA on the magnetic porous microspheres. Specifically, the amount of AA in step S401 was set to 300, 400, 500 and 800 μL, respectively, to obtain magnetic porous microspheres AA-1, AA-2, AA-3 and AA-4.
[0113] Fig.10 The SEM image of magnetic porous microspheres AA-2. Fig.10 It can be seen that the magnetic porous microspheres have uniform particle size, uniform dispersion, very few impurities, and high yield. At the same time, the thickness of the functional group coating layer is adjustable, and the content of the functional group is also adjustable.
[0114] Fig.11 TEM images of magnetic porous microspheres, where (a) is a TEM image of magnetic porous microspheres AA-1 prepared when the AA dosage is 300 μL, (b) is a TEM image of magnetic porous microspheres AA-2 prepared when the AA dosage is 400 μL, (c) is a TEM image of magnetic porous microspheres AA-3 prepared when the AA dosage is 500 μL, and (d) is a TEM image of magnetic porous microspheres AA-4 prepared when the AA dosage is 800 μL. As shown in the TEM images, the thickness and content of the carboxyl functional group coating layer gradually increase with the increase in the amount of swelling monomer used. The densely packed porous structure determines that the magnetic porous microspheres have a large surface area, and the more binding sites there are, the more antibody linkages there will be, which can also be highlighted in combination with performance tests. It can be seen from the transmission electron microscopy and scanning electron microscopy images that the particles are monodispersed, without adhesion aggregation and uniform particle size, indicating that the dispersion state is good and the magnetic porous microspheres have good monodispersity.
[0115] Fig.12 The infrared spectrum of the magnetic porous microsphere AA-2 illustrates the presence of carboxyl groups in the product synthesized by the present invention.
[0116] (1601.59,1493.07,1452.31cm -1 : Characteristic peaks of stretching vibration of benzene ring; 758.61, 698.65, 3025.59cm -1 : stretching vibration peak of CH on benzene ring; 2922.68cm -1 :-CH2-; 1729.47cm -1 :C=O;3437.79cm -1 :-OH).
[0117] Experimental Example 2 Performance Test
[0118] 1. Functional group test
[0119] The magnetic porous microspheres (AA-1, AA-2 and AA-3) were used as samples, and the types and contents of carboxyl functional groups were determined from qualitative and quantitative perspectives by characterization methods such as IR and acid-base titration. The carboxyl content of three representative samples of AA-1, AA-2 and AA-3 was quantitatively determined by using an automatic acid-base titrator, and the results are shown in Table 1. The results show that with the increase of the thickness of the carboxyl layer, the carboxyl content gradually increases.
[0120] Table 1 Acid-base titration carboxyl content test table
[0121]
[0122] 2. Specific adsorption performance
[0123] Using magnetic porous microspheres (AA-1, AA-2 and AA-3) and commercial control magnetic beads as samples, the magnetic porous microspheres themselves were tested for specific adsorption by incubating the magnetic porous microspheres without antibody linkage with the protein complex in a chemiluminescence immunoassay, washing, and detecting the luminescence value. The specific adsorption performance of the carboxyl magnetic beads was observed. The results are shown in Table 2.
[0124] Table 2 Carboxyl magnetic beads specific adsorption performance test table
[0125]
[0126] As can be seen from Table 2, the three magnetic beads AA-1, AA-2 and AA-3 have lower background values (background value refers to the background value in the natural state, including the nonspecific binding value caused by non-antigen-antibody specific binding, the smaller the value, the better) compared with the commercial control magnetic beads, and the nonspecific adsorption is small, indicating that the magnetic porous microspheres prepared by the present invention have excellent specific adsorption capacity.
[0127] 3. Nucleic acid extraction performance test
[0128] The magnetic porous microspheres AA-1 and commercial control magnetic beads were used as samples to test the nucleic acid extraction performance. The specific steps include:
[0129] (1) Add 100 μL of the sample to be tested to 250 μL of the working solution, shake it up and down to mix it, and place it in a 55°C dry bath to heat and lyse it for 5 min.
[0130] (2) After centrifugation for 5 seconds, place the centrifuge tube on a magnetic separator for 1 minute, and then remove the supernatant.
[0131] (3) Add 600 μL of extraction reagent II, cover the tube, vortex and mix for about 5 seconds, centrifuge briefly, place the centrifuge tube on a magnetic separator and magnetize for 1 minute, then remove the supernatant.
[0132] (4) After standing for 1 min, remove the remaining liquid at the bottom of the tube by aspirating.
[0133] (5) Add 50–100 μL of elution buffer, cap the tube, vortex to mix for about 5 seconds, and centrifuge briefly.
[0134] (6) Place the centrifuge tube in an 80°C dry bath and heat to elute for 2 min.
[0135] (7) Place the centrifuge tube on a magnetic separator and take out the supernatant for later use.
[0136] (8) Take out the components in the nucleic acid extraction packaging box (purchased from Zhongyuan Huiji Biotechnology Co., Ltd.), shake off the liquid that may be attached to the aluminum film and well wall of the 96-well plate to the bottom of the well, and let it stand for 3-5 minutes for use.
[0137] (9) Carefully tear open the aluminum film of the 96-well deep-well plate and add 15 μL of proteinase K and 200 μL of the sample to be tested to wells AI1-HI and A7-H7, respectively.
[0138] (10) Use a nucleic acid extraction instrument, set up the program, and complete the nucleic acid extraction. The extraction process takes about 9 minutes.
[0139] The results are shown in Table 3. The performance of AA-1 and existing carboxyl magnetic beads of the same particle size are not much different, indicating that the magnetic porous microspheres prepared by the method of the present invention have good nucleic acid extraction performance.
[0140] Table 3 Comparison of nucleic acid extraction performance of carboxyl magnetic beads
[0141]
[0142]
[0143] 4. Magnetic separation efficiency
[0144] Using magnetic porous microspheres AA-1 and commercial control magnetic beads as samples, 1 mL of samples with the same concentration (1 mg / mL) were taken respectively, and magnetic adsorption separation tests were performed using a magnet. Fig.13 For the comparison of magnetic adsorption separation time of commercial magnetic beads, the uniformly dispersed magnetic beads (13a) were completely adsorbed in about 28s under the action of an external magnetic field ( Fig.13 b). Fig.14 Comparison of AA-1 magnetic adsorption separation time, uniformly dispersed magnetic beads ( Fig.14 a) Under the action of an external magnetic field, the adsorption is complete in about 23 seconds ( Fig.14b), after removing the magnet and mixing and shaking, the magnetic beads returned to a uniformly dispersed state, and the magnetism disappeared, indicating that the magnetic porous microspheres prepared by the present invention have excellent magnetic separation efficiency.
[0145] 5. Sedimentation velocity test
[0146] Using magnetic porous microspheres AA-1, AA-2 and commercial control magnetic beads as samples, 1 mL of samples with the same concentration (1 mg / mL) were taken to observe the natural sedimentation rate. Fig.15 As shown, the test tubes are control samples, AA-1 and AA-2 from left to right, wherein Figure (a) is an image of the sample after ultrasonic homogenization and before sedimentation, and Figure (b) is a picture of the magnetic beads after sedimentation after standing for 2 hours. The control magnetic beads (far left) have completed half of the sedimentation, while only a few of AA-1 and AA-2 have settled and are still in a dispersed state, indicating that the magnetic porous microspheres prepared by the present invention have a slow sedimentation rate and can be more fully combined with antigens and antibodies. The magnetic separation effect of the magnetic beads synthesized by the new multi-step seed growth method is also very good, which can meet the requirements of higher-speed instrument testing and fully improve the product performance of the magnetic porous microspheres.
Claims
1. A method for preparing magnetic porous microspheres for in vitro diagnosis, characterized in that: First, styrene is used as a polymerization monomer and a dispersion polymerization method is used to prepare porous polystyrene microspheres. Iron salt is selected as a precursor and a co-precipitation method is used to synthesize magnetic nanomaterials under alkaline conditions. The magnetic nanomaterials are loaded on the surface and pores of porous polystyrene microspheres through a multi-step seed growth method to obtain magnetic beads. Finally, a monomer containing a functional group is introduced onto the surface of the magnetic ball through a monomer swelling polymerization method to obtain a magnetic porous microsphere.
2. The method for preparing the magnetic porous microspheres for in vitro diagnosis according to claim 1, characterized in that: The magnetic nano material is ferroferric oxide, ferric hydroxide, r-ferrous oxide, ferrate, cobalt oxide, manganese oxide, iron-nickel alloy or iron-aluminum alloy.
3. The method for preparing the magnetic porous microspheres for in vitro diagnosis according to claim 1, characterized in that: The specific steps include: S1. Preparation of polystyrene-based balls: dissolving an initiator, a stabilizer and a polymerizable monomer in an organic solvent at a mass ratio of 0.01-0.5:0.01-0.1:3-10, then heating to 45-55° C. for reaction for 5-7 hours, centrifuging, and drying to obtain polystyrene-based balls; the polymerizable monomer is styrene; S2, preparing porous polystyrene microspheres; S201, mixing a cross-linking agent, a polymerized monomer 1, a polymerized monomer 2, a porogen and a composite emulsifier uniformly to obtain a solution 1; the ratio of the cross-linking agent, the polymerized monomer 1, the polymerized monomer 2, the porogen and the composite emulsifier is 0.05-0.15 g: 2-3 mL: 1-2 mL: 2-3 mL: 25-35 mL; the polymerized monomer 2 is hydroxyethyl methacrylate; S202, dispersing polystyrene base balls in a composite emulsifier at a ratio of 0.2-0.25 g: 110-130 mL at 60-80° C. to obtain solution 2; adding solution 1 to solution 2 at a volume ratio of 35-40: 110-130, reacting at 60-80° C. for 1-3 hours to obtain solution 3; S203, mixing the composite emulsifier, the crosslinking agent, the porogen, the initiator and the solution three in a volume ratio of 8-12:11-14:1-1.5:0.06-0.1:150-165, and then reacting at 80-90° C. for 0.1-1h; S204, centrifuging and drying to obtain porous polystyrene microspheres; S3, magnetospheric envelope; S301, dispersing porous polystyrene microspheres in a composite emulsifier, then adding an iron salt solution under a protective atmosphere, stirring and reacting at 0-70°C for 0.5-1.5h, then adjusting the pH value of the reaction system to 9-12, continuing the reaction for 4-6h, and finally magnetically separating to obtain a magnetic nanomaterial; the ratio of the porous polystyrene microspheres, the composite emulsifier and the iron salt solution is 0.4-0.6g:15-25mL:5-7mL; S302, dispersing the magnetic nanomaterial in a composite emulsifier, and repeating step S301 to obtain multi-layer coated magnetic beads; S4, coating functional group; S401, mixing a composite emulsifier, an initiator, a polymerization monomer 1, a crosslinking agent and a functional monomer in a ratio of 18-22 mL: 0.05-0.15 g: 0.5-1.5 mL: 200-400 μL: 300-500 μL to obtain a solution 4; the functional monomer is styrene, divinylbenzene, 2,4-dichlorostyrene, acrylic acid, methacrylic acid, acrylamide, methyl methacrylate, methyl acrylate, ethyl acrylate, vinyl acetate or glycidyl methacrylate; S402, dispersing the magnetic beads in the composite emulsifier, and then mixing evenly with solution four, then heating to 60-80°C for reaction for 1.5-2.5h, centrifuging, and drying to obtain magnetic porous microspheres; the ratio of the magnetic beads, composite emulsifier and solution four is 0.3-0.7g:30-50mL:20-25mL.
4. The method for preparing the magnetic porous microspheres for in vitro diagnosis according to claim 3, characterized in that: The initiator is at least one of ammonium persulfate, benzoyl peroxide, potassium persulfate, sodium persulfate, sodium sulfite, azobisisobutyronitrile, azobiscyanovaleric acid, sodium bisulfite and dicumyl peroxide; and the stabilizer is polyvinyl pyrrolidone.
5. The method for preparing magnetic porous microspheres for in vitro diagnosis according to claim 3, characterized in that: The crosslinking agent is divinylbenzene or tert-butyl peroxide; the porogen is at least one of toluene, ethylbenzene, n-hexane, cyclohexanol, n-heptane, n-octane, n-heptanol, di(2-ethylhexyl) phosphate and phthalate.
6. The method for preparing the in vitro diagnostic magnetic porous microspheres according to claim 3, characterized in that: The composite emulsifier is prepared by dissolving component A and component B in water at a mass ratio of 0.01-0.12:0.05-1.2; component A is at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium stearate and oleate; and component B is at least one of PVPk30, PVP k60, PVP k80 and PVA.
7. The method for preparing magnetic porous microspheres for in vitro diagnosis according to claim 3, characterized in that: The solutes in the iron salt solution are ferric chloride and ferrous sulfate, and the mass ratio of the ferric chloride to ferrous sulfate is 1-2:
2.
8. The method for preparing magnetic porous microspheres for in vitro diagnosis according to claim 3, characterized in that: The reagent used for adjusting the pH value in S301 is ammonia water, sodium hydroxide, potassium hydroxide, sodium alcoholate or potassium alcoholate.
9. A magnetic porous microsphere for in vitro diagnosis, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the in vitro diagnostic magnetic porous microspheres according to claim 9 in the preparation of in vitro diagnostic reagents.
Citation Information
Patent Citations
Magnetic fluorescent polymer microsphere with high load stability and preparation method of magnetic fluorescent polymer microsphere
CN104262812A
Novel preparation method of functionalized porous magnetic microspheres
CN112175150A
Monodisperse magnetic microspheres
CN112592423A
Preparation method of aminated magnetic microspheres
CN112707995A
Preparation method of porous magnetic polymer microspheres
CN116444730A
Cited By
Magnetic porous microsphere for in-vitro diagnosis and preparation method thereof
CN121847010A